What do Inuit drawings mean to Nisga'a children? - Izu, Yuka (Author); Mills, Antonia (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2003)
No abstract available. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1232059